Supply Chain Management in Tourism: Tunku Abdul Rahman Park, Kota Kinabalu, Sabah - Sun Fatt, Boyd; Alif Amri Nik Hashim, Nik; Kassim, Edi Rizal; Muhammad Safri, Fauzan Hafiz; Maizana Mat Nawi, Nor; Samengon, Harnidah; Kumar Velayuthan, Sathish; Hafizah Muhammad, Nur (International Journal of Supply Chain Management, 2020)
Abstract— Supply chain tourism has become one of the world’s major travel activities. In Sabah, it is one of the main contributors to the state’s economy as most travellers visiting Sabah will engage in this type of tourism. In order to acknowledge the services and activities offered, a study was carried out to determine the local Sabahan visitors’ perception toward the supply chain tourism activities offered at Tunku Abdul Rahman Park. In addition, the study highlighted the impacts of those supply chain activities on the island’s environment. A self-administrated questionnaire was used as the main data collection tool. It was distributed to local visitors on four islands of Tunku Abdul Rahman Park, namely Manukan, Mamutik, Sapi and Gaya Island. The results of the study indicated that most of the local Sabahan visitors were aware of the existence of supply chain tourism activities, and they were satisfied with the services offered at Tunku Abdul Rahman Park. The study also revealed that the supply chain activities would not bring harm to the environment as they perceived the activities would bring benefit to the economy. However, there is an urgency to improve the amenities and signage on the islands involved. This current study is beneficial for policymakers and tourism operators in Malaysia, particularly Sabah. The study’s findings have given perceptive evidence and data for Sabah Park management and Sabah Tourism Board to outline promotional approaches that can entice more tourists to visit the island in future and to sustain the islands’ environment for the long term.